MODEL BAROMETER KINERJA PEMERINTAH BERBASIS LINGKUNGAN USAHA (Kasus Kota Bekasi) - Puguh Suharso (Jurnal Rekayasa Lingkungan)
Reformation democracy guides Indonesian government in one decade of duration, even a little bit more, and also in that time it brings the autonomy region existent with aims to spread out development. Based on this concept that the justice of development of every region can be achieved no exception, and then Indonesian government is able to be an advanced country. Due to Indonesian wish to be an advanced country, the academic society right now has very critical opinion to discuss on ever any scientifi c meeting about how to measure the achievement of a good government performance. To evaluate government performance, an instrument is needed to measure governmentactivities, which that measurement must be based on the determinant object. In this case that the determinant object is an environment of entrepreneur as indicator of measurement. The output of measurement can be used as well as input to government to make decision, then implication of policy can be made. In order to apply that instrument, so must be taken an sample district ascase i.e â€œPemerintah Kota Bekasiâ€. The conclusion of this assessment are : Public services for permission of trade in Kota Bekasi must be improved. Public services in specifi cally for wealth of intelectual right must be improved(clearly in law). A minimum substance wage of district / region must be improved. Rearrangement to taxation has to soon be done. There is more information about assessments conclusion.Ket words : Model, environment of entrepreneur